Analysis of Role Play in Children’s Social-Emotional Development at Madrasah Diniyah Istiqomah Tanah Kusir - Nur Assyifa; Erna Fauziah (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study aims to describe the implementation of the role play method in developing the social-emotional abilities of early childhood at Madrasah Diniyah Istiqomah Tanah Kusir. A descriptive qualitative approach was employed, involving 49 children aged 4–6 years as research subjects, along with two teachers and two parents as key informants. Data were collected through interviews, observations, and documentation, and then analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that role play activities have a positive impact on children’s social-emotional development. Children become more confident, are able to communicate effectively, collaborate with peers, and demonstrate empathy as well as improved emotional regulation. Teachers play a crucial role in facilitating these activities and instilling Islamic values, while parental support further reinforces the application of positive behaviors in the home environment. Therefore, the role play method is proven to be effective as a holistic and contextual learning strategy oriented toward the development of social-emotional character in early childhood within the madrasah diniyah setting.